What effects do macroeconomic conditions have on families' time together? - Melinda Sandler Morill; Sabrina Wulff Pabilonia (Institute for the Study of Labor (IZA), 2012)
We examine family time together using data from the 2003-2010 American Time Use Survey combined with Bureau of Labor Statistics data on state-level unemployment rates. Couple time together is U-shaped; while fathers spend more time engaging in enriching childcare activities without a spouse present as the unemployment rate rises. Patterns are similar for dual-earner couples, but appear concentrated among demographic groups most affected by recessions. We also find that mothers are less likely to work standard hours and more likely to work on weekends as employment crises deepen, which is consistent with both sets of results for family time together.
urn:nbn:de:101:1-2012081412617
Keywords: D1; J22; J12; E32; 330; unemployment; time use; time together; Great Recession; nonstandard work hours; Familie; Zeitverwendung; Konjunktur; Arbeitslosigkeit; USA